Lyell’s syndrome: a rare case report - Rao Venkata Mahipathy, Surya Rao; Durairaj, Alagar Raja; Sundaramurthy, Narayanamurthy; Ramachandran, Manimaran; Natarajan, Praveen Ganesh (International Surgery Journal, 2019)
Lyell’s syndrome or toxic epidermal necrolysis (TEN) is an epidermal detachment of more than 30% of total body surface area, most commonly due an idiosyncratic immune-allergic reaction to a drug. It causes an acute necrosis of the epidermis, with a clinical picture resembling extensive burns. There is also associated mucosal damage and can occasionally develop into a multiorgan having a poor prognosis. Here we report a case of toxic epidermal necrolysis, due to allopurinol intake and its management as in a large burns and stressing the importance of early treatment in an intensive care unit, with high vigil on fluid and electrolyte balance, prevention and treatment of infection with appropriate antibiotics and regular dressings.